2020
DOI: 10.31557/apjcp.2020.21.7.2067
|View full text |Cite
|
Sign up to set email alerts
|

Ki67, CD105, and α-SMA Expression Supports Biological Distinctness of Oral Squamous Cell Carcinoma Arising in the Background of Oral Submucous Fibrosis

Abstract: Background: The clinicopathological distinctness of oral squamous cell carcinoma arising in the background of oral submucous fibrosis (OSCC-OSF) is well known; however, the molecular distinctness of this unique OSCC-OSF has not been investigated to date. With this in mind, we compared the expression of Ki67 , CD105 , and α-SMA between OSCC-OSF and oral squamous cell carcinoma (OSCC). Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…These included following lesions-UDH, ADH, and DCIS. Similar related studies were reported [14][15][16][17]. Studies reported by Yeola et al [18,19] Anand et al [20] were reviewed.…”
Section: Discussionsupporting
confidence: 64%
“…These included following lesions-UDH, ADH, and DCIS. Similar related studies were reported [14][15][16][17]. Studies reported by Yeola et al [18,19] Anand et al [20] were reviewed.…”
Section: Discussionsupporting
confidence: 64%
“…After the duplicates were removed and exclusion of 2255 records due to coherence with the inclusion/exclusion criteria, 208 articles relevant to the topic were accurately evaluated. Two records were unavailable for retrieval; thus, 206 articles were assessed for eligibility, and 84 were included in the review [ 19 , 26 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ,...…”
Section: Resultsmentioning
confidence: 99%
“…All the 84 studies included in the qualitative analysis were ex vivo tissue investigations based on histopathological analysis of tumor biopsies or surgical specimens [ 19 , 26 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ,...…”
Section: Resultsmentioning
confidence: 99%
“…The staining procedures were sequentially carried out on the section of the lymph nodes i.e. Histopathological examination using formalin fixed tissue: conventional H and E staining A number of studies on related aspects of oral squamous cell carcinoma and lymph node metastasis were reported [20][21][22][23]. Agrawal et.…”
Section: Reconstruction Using Suitable Flapmentioning
confidence: 99%